A Large Scale Application of Slon Magnetic Separator in Meishan Iron Ore Mine. (2002) - Dahe, Xiong
Abstract : Meishan Iron Mine processes 4 million tons of iron ore and produces about 2.6 million tons of iron concentrate annually. Because of a relatively high content of phosphorus, the iron concentrate does not meet the market requirements. In recent years, 18 SLon- 1500 magnetic separators have been applied to reduce phosphorus to upgrade the concentrate quality. This paper describes research, test work and industrial application of SLon magnetic separator in the mine.